Impact of the 2020 COVID-19 Pandemic on Ambulatory Hepatitis C Testing. (November 2020) - Sperring, Heather; Ruiz-Mercado, Glorimar; Schechter-Perkins, Elissa M.
Introduction: Coronavirus disease 2019 (COVID-19) has led to unprecedented modifications to healthcare delivery in the U.S. To preserve resources in preparation for a COVID-19 surge, Boston Medical Center (BMC) implemented workflows to decrease ambulatory in-person visits effective March 16th, 2020. Telemedicine was incorporated into clinical workflows and much preventive care, including Hepatitis C (HCV) testing, was not routinely performed. Objective: To explore the impact that the COVID-19 rapid restructuring response has had on HCV testing and identification hospital-wide and in ambulatory settings. Methods: BMC utilizes reflex confirmatory testing for HCV. When a sample is HCV Ab positive, it is automatically reflexed for confirmatory RNA and genotype testing. HCV test results for patients were collected daily. We compared unique patient tests for 3.5 month periods before and after March 16th, 2020. Descriptive statistics showed total tests and total new HCV RNA+ before versus after, both hospital-wide and in ambulatory clinics alone. Mean daily tests completed were compared. Results: Hospital-wide, total HCV testing decreased by 49.6%, and new HCV+ patient identification decreased by 42.1%. In ambulatory clinics, testing decreased by 71.9%, and new HCV+ identification decreased by 63.3%. Hospital-wide, mean daily tests decreased by 22.9 tests per day (95% CI: 17.9-28.0, P < .001), and mean daily new HCV+ identification decreased by 0.36 (95% CI: 0.20-0.53, P < .001). In ambulatory clinics, mean daily tests decreased by 22.1 tests per day (95% CI: 17.5-26.7, P < .001) and mean daily HCV+ decreased by 1.40 (95% CI: 1.03-1.76, P < .001). Conclusion: The COVID-19 systematic emergency response led to decreased HCV testing and identification, and in this regard telemedicine acts as a barrier to HCV care. Other public health initiatives must be monitored in the context of telemedicine workflows. Continued monitoring of HCV screening trends is vital, and adaptive approaches to work toward the goal of HCV elimination are needed.